The story «Totynama» and its variants in Uzbek literature - Omarov, Бауыржан (Turkic Studies Journal, 2021)
«Totynama» is one of the most famous literary monuments in the world, which has many variants and is still of interest to researchers. This famous work, widely distributed in many countries, had a sufficient number of authors in different historical periods. The collection of stories «Totynama» by Ziyauddin Nakhshabi, which received special recognition in world literature and has a high artistic value, became a solid basis for the creation of many later versions of this unique creation. Therefore, thanks to the writers who translated into their languages and masterfully finalized this work, several completely new readings of it appeared. The Nakhshabi variant also gained popularity in Central Asia, the cradle of scribal poets who sought inspiration from the Eastern literary tradition. Among the states of this region, Uzbekistan occupies a special place, where the ancient manuscripts of «Totynama» are carefully preserved and the heritage of the people is fully used. At the same time, in the Uzbek literature, there are other works dating back to the work of Nakhshabi and called «Totynama». The prose version of «Totynama» by Latifi and its poetic version, which came out from the pen of Khiromi, undoubtedly became valuable creations that elevate Uzbek literature. This article analyzes various information and sources, scientific works devoted to the story «Totynama» in a neighboring country. The author presented his conclusions about the peculiarities of the variants of «Totynama» widespread in Uzbekistan, the significance and artistic value of these literary monuments.